Ta có:
$\frac{x}{a+2b+c}=\frac{y}{2a+b-c}=\frac{z}{4a-4b+c}$
$\rightarrow \frac{x}{a+2b+c}=\frac{2y}{4a+2b-2c}=\frac{z}{4a-4b+c}$
Áp dụng tính chất của day tỉ số bằng nhau ta có:
$\frac{x}{a+2b+c}=\frac{2y}{2a+b-c}=\frac{z}{4a-4b+c}=\frac{x+2y+z}{a+2b+c+4a+2b-2c+4a-4b+c}=\frac{x+2y+z}{9a}(1)$
Lại có:
$\frac{x}{a+2b+c}=\frac{y}{2a+b-c}=\frac{z}{4a-4b+c}$
$\frac{2x}{2a+4b+2c}=\frac{y}{2a+b-c}=\frac{z}{4a-4b+c}$
Áp dụng tính chất của dãy tỉ số bằng nhau ta có:
$\frac{2x}{2a+4b+2c}=\frac{y}{2a+b-c}=\frac{z}{4a-4b+c}=\frac{2x+y-z}{2a+4b+2c+2a+b-c-4a+4b-c}=\frac{2x+y-z}{9b}
(2)$
Ta lại có:
$\frac{x}{a+2b+c}=\frac{y}{2a+b-c}=\frac{z}{4a-4b+c}$
$\frac{4x}{4a+8b+4c}=\frac{4y}{8a+4b-4c}=\frac{z}{4a-4b+c}$
Áp dụng tính chất của dãy tỉ số bằng nhau ta có:
$\frac{4x}{4a+8b+4c}=\frac{4y}{8a+4b-4c}=\frac{z}{4a-4b+c}=\frac{4x-4y+z}{4a+8b+4c-8a-4b+4c+4a-4b+c}=\frac{4x-
4y+z}{9c}(3)$
Từ (1);(2);(3) ta có $\frac{x+2y+z}{9a}=\frac{2x+y-z}{9b}=\frac{4x-4y+z}{9c}(bằng \ đẳng \ thức \ GT)$
$\rightarrow \frac{9a}{x+2y+z}=\frac{9b}{2x+y-z}=\frac{9c}{4x-4y+z}$
$\rightarrow \frac{a}{x+2y+z}=\frac{b}{2x+y-z}=\frac{c}{4x-4y+z}(dpcm)$